Nilai-Nilai Pendidikan Islam dalam Buku Seni Tinggal Di Bumi Karya Farah Qoonit - Nuryanti, Aan; Ainusyamsi, Fadlil Yani; Rizal, Soni Samsu (Fakultas Tarbiyah, Institut Agama Islam Darussalam (IAID), Ciamis, Jawa Barat, Indonesia, 2020)
This study aims to (1) find out the general description of the story in Farah Qoonita's book The Art of Living on Earth. (2) To find out the values ​​of Islamic education contained in the book Art of Living on Earth by Farah Qoonita. This type of research is qualitative research which is literature study using other literature books as the main object. The data collection method used in this research is the documentation method. In this research, the documentation method. In this study, the documentation method was used to obtain data about the values ​​of Islamic education contained in Farah Qoonita's book The Art of Living on Earth. The author takes notes, observes, and questions and answers. After the data is collected, then the data is separated, selected, and grouped. The results of the study show: (1) The general description of the book Art of living on Earth is to tell a story about lessons learned from the surrounding environment, history, religion, politics, women, to humanity. how to live in a piece of His kingdom, then we must know how the art of living there starts from how we carve each colorful brush stroke on the canvas of life. (2) The values ​​of Islamic Education in the art book Staying on Earth: first, patience is a useful trait to control the trials given by Allah. Second, gratitude is acknowledgment of the blessings given by Allah SWT accompanied by submitting to Him and using these blessings according to Allah's will. Third, praying means calling, calling, or asking Allah for help for everything that is desired.